Building a shared agenda for climate risk management - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Workshop held by the Honduran Secretary of Agriculture (SAG), The United Nations Environment Programme (UNEP) office in Honduras and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) about the status of climate risk management and National Food Security